141 USING A TEMPLATE TO IMPROVE COMMUNICATION ON DISCHARGE LETTERS REGARDING BONE PROTECTION THERAPY AFTER HIP FRACTURE. (18th November 2021) - Doyle, K; McManus, C; O'Brien, M; Brewer, L
Abstract: Background: Hip fractures are a significant cause of morbidity and mortality amongst older adults. The Irish Hip Fracture Database Standard 5 requires that all patients with hip fracture have a bone health assessment completed; most are commenced on bone protection therapy (BPT) to reduce future fractures. Communication to general practitioners (GPs) regarding long-term BPT is often incomplete and challenging to improve. We aimed to upgrade this communication process at discharge. Methods: Initial audit was conducted assessing documentation of BPT after hip fracture in discharge letters to GPs. Subsequently we created a detailed BPT template for discharge letters containing clear information for GPs regarding medication initiation and advice for ongoing management. The template was introduced and doctors were educated on its use. We then re-audited discharge letters following this intervention. Patients included were over 60 years old with hip fracture. Patients deemed clinically unsuitable for BPT were excluded. Results: Ninety discharge letters were reviewed, 45 at initial audit and another 45 after introducing the BPT template. Mean age was 80 years old, 66 (73%) were female. In the first audit cycle, 28/45 discharge letters (62%) briefly specified BPT. On repeating the audit cycle (following introduction of the discharge letter template) all 45/45 discharge letters (100%) clearly specified BPT. Most letters (41/45; 91%) included the detailed BPT template. Following this intervention all doctors reported increased awareness and understanding of BPT, and satisfaction with template use in discharge letters. Conclusion: Effective implementation of a discharge letter template significantly improved communication to GPs regarding BPT following hip fracture.